Active versus Passive Equity Fund Performance in Indonesia: Evidence from Risk-Adjusted Measures and Manager Fees (2018–2025) - Erika Marthalina Sitorus; Maria Ulpah (Owner : Riset dan Jurnal Akuntansi, 2026)
This study examines whether actively managed Indonesian equity mutual funds deliver superior net-of-fee, risk-adjusted performance compared to the Jakarta Composite Index (JCI) as a proxy for passive investment. Using a quantitative approach, the analysis covers 119 conventional Indonesian equity mutual funds over the period 2018–2025, encompassing pre-COVID, COVID, and post-COVID market regimes. Risk-adjusted performance is evaluated using the CAPM-based Single Index Model and a matrix of Sharpe ratio, Treynor ratio, and Jensen’s alpha, with non-parametric statistical tests applied to assess performance differentials. The results indicate that, after fees, active equity mutual funds underperform the JCI benchmark across most performance measures, with median Sharpe ratios and Jensen’s alphas not statistically different from or lower than the benchmark. Evidence of partial market efficiency and widespread closet indexing is observed, while any behavioural mispricing appears insufficient to generate persistent alpha capable of offsetting higher management and expense fees. These findings suggest that active management does not provide significant added value in the Indonesian equity market over the long term. Investors may benefit more from passive investment strategies, while regulators are encouraged to enhance fee transparency and performance disclosure to support informed investment decisions.